A critical inquiry into sexual networks in Marange District, a case study of Johane Marange Apostolic Church community in Marange, Zimbabwe. - Mavunganidze, Talent Celia (My University, 2009)
The study is an inquiry of sexual networks in the Johanne Marange apostolic community. The study is a conceptual shift in the study of HIV transmission, with focus moving beyond the individual and beyond the principles of desire, pleasure and procreation to a study of sexual networks which are social structures. The study identifies the type of sexual networks and further investigates the determinants of sexual networks in Marange community. Sexual networks are simply webs of sexual relations in a community or society and these webs of relations act as transmission highways for HIV. The study discusses all the complex interactions between the domain of society that is religion, culture, history and environment of the Marange community and uncovers how these aspects of society have influenced the shape and structure of sexual networks in the community. The study also emphasizes the importance of understanding sexual network structure as it influences the efficiency of HIV transmission and aims to contribute to a better understanding of sexual networks and HIV transmission.
Keywords: Sexual networks; HIV/AIDS; Zimbabwe